Kelestarian Pelancongan Peribumi: Satu Kajian Kes di Tapah Perak (Sains Humanika, 2018)
This paper discusses the sustainability of native tourism in Tapah, Perak. This study is important because studies related to indigenous tourism are still not widely explored, especially in Malaysia. This study uses purposive sampling. Data are also collected using in-depth and detailed structured interviews. The big impact can be seen through the economic capital to carry out this indigenous tourism. Economic capital contributes to the economic strength of indigenous people’s. Through the economic strengths supported by the local agencies, it can lead to continuous improvement of the economic capital of the Orang Asli of the Semai tribe tapah, Perak, as well as contributing to the sustainability of native tourism in the area.
Keywords: Sustainability; Native Tourism; case studies; economic capital; science